Word 2016 - Marmel, Elaine J. (Indiana polis John Wiley and Sons, 2016)
Provides clear, step-by-step instructions for tackling more than 160 Word 2016 tasks. Each task-based spread covers a single technique, sure to help you get up and running on Word 2016 in no time.--
Getting familiar with Word -- Managing documents -- Editing text -- Proofreading -- Formatting text -- Formatting paragraphs -- Formatting pages -- Printing documents -- Working with tables and charts -- Working with graphics -- Customizing Word -- Working with mass mailing tools -- Word and the world beyond your desktop.
"The fast and easy way to learn"--Cover.
Includes index.
Keywords: Microsoft Word; Microsoft Word; Word processing; Word processing